Penyuluhan Membuat Lampu Emergency Kepada Karang Taruna Merpati Putih Rt 004. Rw 04 Condet Kramat Jati Jakarta Timur - Rosalina; Nunik Pratiwi; Akhmad Haqiqi Ma’mun (Jurnal SOLMA, 2021)
Karang Taruna Merpati Putih is located on the highway Condet kec. Kramat Jati, East Jakarta, is a youth organization that has not been enthusiastic about being creative in terms of creating production as a joint business opportunity. The highlight of the community service this time is on the problem of how to increase the level of knowledge of the leaders and members of the youth organization towards the development of the creative industries of youth. From this activity it is hoped that it can provide enlightenment motivation to become a business entrepreneur. Motivation, enthusiasm and the sincere will of the members of the Youth Organization is very important to achieve a form of skill that is of positive value so that it can spawn creative industries for the advancement of the nation. motivating the enthusiasm and willingness of the members of the youth to dare to work. One of the knowledge and skills to develop the existing potential is to provide training in making a simple electronic circuit that is making a series of emergency lights (Light Emitting Diodes / LEDs) which are commonly used as a source of light for PLN electricity substitutes.